PENGUKURAN RENDEMEN DAN IDENTIFIKASI SENYAWA METABOLIT SEKUNDER PADA EKSTRAK DAUN TERAP (Artocarpus odoratissimus Blanco) DENGAN VARIASI PELARUT - anna khumaira sari; Dwi Rizki Febrianti; muhammad fikri (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2019)
Terap plant have abundant health benefits. In the community of leaf terap empirically used as a lowering of high blood pressure by boiling a few leaves and then drinking boiled water. In this study the aim was to find out what percentage of yield obtained in leaf extracts applied with methanol, ethyl acetate and n-hexane solvents and any secondary metabolites contained in each extract. The type of research used in this study is non-experimental with a descriptive method which describes how much yield obtained in leaf extract using maceration method and using methanol, ethyl acetate and n-hexane solvents and then any secondary metabolites contained in the extract the leaves are applied with methanol, ethyl acetate and n-hexane solvents. The sample used is a plant from Banjang Village.. This study the management of the data used is qualitative. The results showed that the leaf extract with the methanol produced the largest yield of 13.57%, with secondary metabolite compounds flavonoids, tannins, quinones, saponins, and phenols, then with ethyl acetate solvents produced a yield of 5.52%, with content of secondary metabolites of flavonoids, tannins, phenols and quinones, while the smallest yields were n-hexane solvents, which is 2.30%, with triterpenoid and quinone secondary metabolites.